Quality and accreditation in higher education: integration and internationalization of Latin America and the Caribbean - Jorge González González; Rocío Santamaría Ambriz (Pontificia Universidad Católica del Perú, 2013)
The paper discusses the concepts of «quality» and «accreditation» in education with different meanings, and proposes comprehensive definitions that have been put into practice by the Union of Universities of Latin America and the Caribbean and the International Network of Evaluators through model «V» evaluation planningfor continuous improvement, integration and internationalization of higher education.